UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SEJARAHMELALUI MODEL PEMBELAJARAN GROUP INVESTIGATION PADA SISWAKELAS XI IPS 1 SMA ADIGUNA BANDAR LAMPUNG - Muhammad, Muhammad (STKIP PGRI Bandar Lampung, 2019)
The purpose of this research was to increase the activity and learning outcomes of History. This research is a Classroom Action Research that is the process of learning problems in the classroom through self-reflection in an effort to solve these problems by carrying out various planned actions in real situations and analyzing each effect of the treatment. This research was designed in each cycle consisting of the stages of planning, implementation, observation, evaluation and analysis and reflection of actions. The research subjects were 22 students of class XI IPS 1 of SMA Adiguna Bandar Lampung in the 2015/2016 Academic Year. Data collecting techniques using observation sheets, test techniques and documentation. The results showed an increase in learning activities and students’ learning outcomes each cycle, student learning activities in the initial conditions there were only 8 students or 36.36% increased to 14 students or 63.64% and 20 students or 90.91% in the last cycle. Thus, the average student learning outcomes also increased in each cycle from 62.25 increased to 72.05 in the first cycle and at the end of the second cycle increased to 79.55.